Health-related quality of life profile in relation to chemotherapy-induced nausea and vomiting among breast cancer patients - Pei, Lin Lua; Zakaria, Noor Salihah; Mamat, Nik Mazlan (ASEAN Federation of Psychiatry, 2012)
Objective: Despite the availability of modern anti-emetics, chemotherapy-induced nausea and vomiting (CINV) symptoms remain distressing to a high number of cancer patients. This study intended to (1) describe the incidence of CINV and anti-emetic usage; (2) assess the health-related quality of life (HRQoL) and correlate its components with Global Health Status; (3) evaluate HRQoL status in relation to CINV among breast cancer patients receiving chemotherapy. Methods: A cross sectional study was conducted in two government hospitals located in the East Coast of Peninsular Malaysia (Terengganu, Kelantan). The Morrow Assessment of Nausea and Emesis Follow-up (MANE-FU) and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) were administered. Descriptive statistics and non-parametric tests were employed (SPSS 16). Results: Respondents included 41 female patients (age = 49 ± 9.6 years; Malay = 92.7%; no family history of breast cancer = 68.3% and on moderately emetogenic chemotherapy = 97.6%). Majority of patients experienced nausea during or after chemotherapy (90.2%) and rated it as ‘severe’. Most patients had taken anti-emetic (87.8%) and considered it ‘somewhat useful’. The median score for Global Health Status was 50 (IqR= 16.7). Emotional Functioning, Fatigue and Pain correlated fairly with HRQoL (rs= +0.435; -0.417; -0.387 respectively). Patients with ‘a lot’ and ‘moderate’ nausea displayed significantly more fatigue compared to those with little nausea (p=0.029). Those who experienced vomiting reported worse HRQoL profile compared to those who did not (p=0.011). Conclusion: These findings generally ascertained that CINV remains poorly controlled and significantly interferes with HRQoL, providing rooms for improvements in therapeutic intervention.